Efektifitas Implementasi Pembelajaran Daring Pada Masa Pandemi Covid-19 Di Sekolah Dasar 010 Minas - Ayu Listian Tarigan (Proseding Didaktis: Seminar Nasional Pendidikan Dasar, 2020)
This study aims to identify the implementation of online learning at home for elementary school students due to the COVID-19 pandemic. This research uses library research where in collecting data information with documentation techniques, namely looking for data about relevant matters from various kinds in the library such as documents, books, magazines, news. The criteria for the articles and news chosen were discussion of the impact of COVID 19 and online learning in elementary schools. From the 15 sources obtained, then the most relevant were selected and 3 articles and 5 news items were selected. The results in the study show that the impact of COVID-19 on the implementation of online learning in elementary schools can be implemented quite well. This can be seen from the results of data from 3 articles and 6 news which show that the impact of COVID-19 on the implementation of online learning in elementary schools can be carried out quite well if there is collaboration between teachers, students and parents in learning at home